Problem the invisible work of women and the sexual division of work in the field: a partnership between popular education and feminism - Carla Negretto; Márcia Alves da Silva (Universidade Federal do Norte do Tocantins, 2018)
Historically, peasant women, as well as urban women, suffer from gender inequality. Thus the patriarchal system that reinforces the sexual division of labor sums up the lives of many women, both domination and exploitation, and the sole responsibility for household chores and childcare. This article develops some reflections that refer to an investigative experience that the author has been developing since the year 2014 with women based on Agrarian Reform and whose objective is to problematize gender and power relations related to the sexual division of labor between men and women of 2 settlements of Agrarian Reform located in the interior of the municipality of Pinheiro Machado/RS. It is intended to explore social space and life experiences, giving women voice on their life and work trajectories, discussing with the male public aspects of social reproduction that divides assignments, tasks and places for men and women. For the purpose of this proposal, this participatory research attentive to the methods of Popular Education and Feminist studies that allow dynamic and modifiable moments directed towards a social transformation.